Adopting Soft Logic to enhance an Adizes tool: A comprehensive approach to represent the evaluation of management styles - Sigal Kordova; Ron S. Hirschprung (PLoS ONE, 2025)
Management skills assessment has become increasingly complex in today’s digital age, as these skills are multi-dimensional and require a nuanced approach. Beyond evaluating each dimension independently, it is crucial to consider the tension and balance between them, as they often exist in inverse proportions. To address this complexity, this study introduces a methodology based on Soft Logic, a mathematical theory designed to represent realities that are not clear-cut, such as conflicting traits. This approach is particularly suited to the assessment of managerial skills. The research focuses on the Adizes Management Style Questionnaire, a widely recognized tool that evaluates four distinct managerial styles: Producer, Administrator, Entrepreneur, and Integrator. Unlike traditional assessments that focus on isolated behaviors, the proposed method highlights the dynamic interplay between these styles. By incorporating Soft Logic, the framework provides a more flexible and comprehensive evaluation, capturing both dominant traits and the tensions between them. This methodology was tested in an empirical study with 40 participants and offers organizations deeper insights into leadership dynamics, aiding in recruitment, leadership development, and team composition. Although developed with the Adizes tool, the methodology can be adapted to other managerial assessment tools and potentially extended to other multi-dimensional domains.